‘Aisyah Kritikus Hadis Pertama dalam Islam - Ahmad Fudhaili (ILMU USHULUDDIN, 2018)
Gender is not a factor that determines a person’s position in the academic/scientific, socio-cultural or socio-religious world, actions or achievements in academic/scientific, socio-cultural or socio-religious life are what determine a person’s position, male or female. The Prophet’s expression: “Appearance (ṣuar), wealth (al-māl) is not the basis for Allah’s judgment, but it is your heart (qulūb) and deeds (a’māl) that are the basis of Allah’s judgment.” (HR. Muslim), Hadith is not just a wise sentence that adorns Islamic religious literature and becomes a formal legal expression that is believed to be true, but the sentence is a spirit, inspiration and motivation for every Muslim to be able to do the best for himself. based on the belief that the whole journey of his life is worship (I did not create the jinn and humans except to worship Me, (al-Dzāriyāt [51]: 56). In hadith literature and hadith science it has been proven that women position themselves at the peak of achievement. the highest that they can achieve, because gender position is not a consideration for rejection or acceptance of a narration of hadith. The quality of a narrator is the main consideration. If there is a contradiction between the narration of a woman and the narration of a man, then the consideration is professionalism and proportionality in the hadith that was reported narrate. This attitude of professionalism has existed since the time of the Prophet Muhammad. and even get support from the teachings of Islam formally.